Conductive polythiophene/graphitic-carbon nitride nanocomposite for the detection of ethanol mixing in petrol. Issue 18 (18th April 2023) - Husain, Ahmad; Ahmad, Sharique; Alqarni, Sara A.; Almehmadi, Samar J.; Yatoo, Mudasir A.; Habib, Faiza; Shariq, Mohd Urooj; Ali khan, Mujahid
Abstract : Conductive polythiophene/graphitic-carbon nitride nanocomposite for the detection of ethanol mixing in petrol. Abstract : The automobile vehicles must be operated on fuel containing no more than 10% ethanol. Use of fuel having more than 10% ethanol may cause engine malfunction, starting and running issues, and material degradation. These negative impacts could cause irreversible damage to the vehicles. Therefore, ethanol mixing in petrol should be controlled below 10% level. The current work is the first to report sensing of ethanol mixing in petrol with reference to the variation in the DC electrical conductivity of polythiophene/graphitic-carbon nitride (PTh/gC3 N4 ) nanocomposite. The in situ chemical oxidative method of polymerization was used for synthesizing PTh and PTh/gC3 N4 nanocomposite. Fourier transform infrared spectroscopy (FT-IR), X-rays diffraction (XRD), thermo-gravimetric analysis (TGA), transmittance electron microscopy (TEM) as well as scanning electron microscopy (SEM) analysis were used for confirmation of the structure along with morphology of the PTh and PTh/gC3 N4 nanocomposite. The thermal stability of DC electrical conductivity of PTh and PTh/gC3 N4 nanocomposite were tested under isothermal and cyclic ageing condition. The sensing response of PTh and PTh/gC3 N4 nanocomposite as a function of DC electrical conductivity were recorded in petrol and ethanol atmosphere. The sensing response of PTh/g-C3 N4 nanocomposite in petrol atmosphere was 6.1 times higher than that of PTh with lower detection limit to 0.005 v/v% of ethanol prepared in n -hexane.